FTire - the tire simulation model for all applications related to vehicle dynamics - Gipser, M. (Vehicle system dynamics, 2007)
The first version of the tire simulation software Flexible ring Tire model (FTire) had been released in December 1998. Being subject to permanent improvement and several far-reaching model extensions since then, today it is one of the most widely used and generally accepted tire models for ride comfort, handling, and road load prediction. Strength of FTire is the strictly physical background, which perfectly fits both to Multi-Body Systems (MBS) and Finite Element Method (FEM) environments. Even though certain simplifications are unavoidable, this clean mechanical, thermo-dynamical, and tribological structure of the model guarantees a consistent and plausible model behavior even in situations that are not covered by respective measurements. The modelization takes into account most of the relevant excitation sources and non-linear transfer mechanisms, up to very high frequencies and extremely short wavelengths. The model's high level of detail is accompanied by a very comfortable program interface and a numerically robust and efficient solver. This allows the simulation of even extreme manoeuvres with moderate computation time. FTire can be used together with most of the important MBS packages and specialized vehicle dynamics programs. This contribution gives an overview on history, application, modelization, road models, parameterization, interfacing, availability, and future perspectives of FTire.